Antioxidative catechol lignans/neolignans isolated from defatted kernel of Jatropha curcas - Toshisada Suzuki (2018)
© 2016, The Japan Wood Research Society. Jatropha curcas L. has been cultivated in many countries for biodiesel production, and defatted kernel is generated in huge quantities as a by-product in the production. This study investigated the phenolic content and antioxidative activity of the defatted kernel of Jatropha. Four extracts, EtOAc-organic, EtOAc-water, MeOH-organic, and MeOH–water fractions, were tested for phenolic content and antioxidative activity using the Folin–Ciocalteu method and the DPPH (2, 2-diphenyl-1-picrylhydrazyl) method, respectively. The MeOH-organic fraction showed a high content of phenolic compounds and exhibited a relatively strong antioxidative activity. Eight compounds were isolated from the MeOH-organic fraction, and identified as a catechol-type lignan (3,3′- bisdemethylpinoresinol), five neolignans (isoamericanol A, americanol A, 9′-O-methylisoamericanol A, 9′-O-methylamericanol A, and isoamericanin A), and two sesquineolignans (isoprincepin, princepin). The antioxidative activities of 3,3′-bisdemethylpinoresinol (IC50: 16.0 μΜ), isoprincepin (9.12 μΜ), and princepin (11.7 μΜ), which have two catechol groups were higher than that of Trolox (21.5 μΜ). The isoamericanol A inhibited the oxidation of biodiesel. These results indicate that the defatted kernel of Jatropha is a source of natural antioxidants that would applicable for stabilizers in Jatropha biodiesel industries.